METHODOLOGY FOR ORGANIZING DRAWING GEOMETRY LESSONS IN AN AUTO CAD GRAPHICS PROGRAM (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article details the methodology for organizing drawing geometry lessons through the AutoCAD graphics program, the use of lectures and practical workshops in engineering graphics subjects on the basis of advanced information technology, and the perfect mastering of modern graphics programs.